2012
DOI: 10.1371/journal.pone.0042629
|View full text |Cite|
|
Sign up to set email alerts
|

Effective Group Training for Patients with Unexplained Physical Symptoms: A Randomized Controlled Trial with a Non-Randomized One-Year Follow-Up

Abstract: BackgroundAlthough cognitive-behavioral therapy for Unexplained Physical Symptoms (UPS) is effective in secondary care, studies done in primary care produced implementation problems and conflicting results. We evaluated the effectiveness of a cognitive-behavioral group training tailored to primary care patients and provided by a secondary community mental-health service reaching out into primary care.Methodology/Principal FindingsThe effectiveness of this training was explored in a randomized controlled trial.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 70 publications
0
23
0
1
Order By: Relevance
“…Apart from chronic pain, arthritis and digestive diseases were also significant physical disorders. Pain disorders and gastrointestinal complaints have been described as some of the most frequent somatic symptoms among the attendees of specialty clinics and are particularly likely to remain unexplained (41), resulting in increasing disability and a higher utilization of health care, which is commonly unsatisfactory (42). The self-perceived health disability of digestive diseases was the highest among all disorders considered herein at the individual level, dropping to fifth in the rank at the societal level due to the low prevalence of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from chronic pain, arthritis and digestive diseases were also significant physical disorders. Pain disorders and gastrointestinal complaints have been described as some of the most frequent somatic symptoms among the attendees of specialty clinics and are particularly likely to remain unexplained (41), resulting in increasing disability and a higher utilization of health care, which is commonly unsatisfactory (42). The self-perceived health disability of digestive diseases was the highest among all disorders considered herein at the individual level, dropping to fifth in the rank at the societal level due to the low prevalence of these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The data for this study came from a randomized controlled trial on the effectiveness of cognitive-behavioral group training (CBT) for patients with UPS [22]. Patients with UPS were randomized either to CBT or to a waiting list after they had completed the baseline measurement (T0).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the PCS was chosen as outcome measurement, because patients reported the quality of life in the physical domain as most burdensome. The group training significantly improved quality of life in the physical domain, and this positive effect was maintained during the entire one-year follow-up period [30]. …”
Section: Methodsmentioning
confidence: 99%
“…Based on previous findings, we aim to detect a clinically relevant effect size of 0.4. This effect size was previously shown to be feasible in a similar population [18]. The clinically relevant difference on the PCS ranges from 3 to 5 points [51].…”
Section: Methodsmentioning
confidence: 99%